Street Artist:: Urban Flanêurie - Lousa, Teresa (Street Art & Urban Creativity, 2015)
It is the goal of this paper to aesthetically rethink Street Art’s artistic process and question its narrative in urban and public space. We intend to highlight the anonymity, ephemeral, and transitory element as a key feature of its artistic creation. To this end, we will use as a starting point the relationship between the street artist and Baudelaire’s flanêur, to reach Foucault’s point of view, which somehow finds the key to the street artist’s aesthetic features, synthesized in the understanding of Baudelaire’s modernity, understood not as a mere historical period, but rather as an “attitude.”